Expert Opinion on the Diagnosis and Management of Male Hypogonadism in India - Kalra, Sanjay; Jacob, Jubbin; Unnikrishnan, A. G.; Bantwal, Ganapathi; Sahoo, Abhay; Sahay, Rakesh; Jindal, Sushil; Agrawal, Madhu Sudan; Kapoor, Nitin; Saboo, Banshi; Tiwaskar, Mangesh; Kochhar, Kapil (International journal of endocrinology, 2023)
Male hypogonadism (MH) is a clinical and biochemical syndrome caused by inadequate synthesis of testosterone. Untreated MH can result in long-term effects, including metabolic, musculoskeletal, mood-related, and reproductive dysfunction. Among Indian men above 40 years of age, the prevalence of MH is 20%–29%. Among men with type 2 diabetes mellitus, 20.7% are found to have hypogonadism. However, due to suboptimal patient-physician communication, MH remains heavily underdiagnosed. For patients with confirmed hypogonadism (either primary or secondary testicular failure), testosterone replacement therapy (TRT) is recommended. Although various formulations exist, optimal TRT remains a considerable challenge as patients often need individually tailored therapeutic strategies. Other challenges include the absence of standardized guidelines on MH for the Indian population, inadequate physician education on MH diagnosis and referral to endocrinologists, and a lack of patient awareness of the long-term effects of MH in relation to comorbidities. Five nationwide advisory board meetings were convened to garner expert opinions on diagnosis, investigations, and available treatment options for MH, as well as the need for a person-centered approach. Experts’ opinions have been formulated into a consensus document with the aim of improving the screening, diagnosis, and therapy of men living with hypogonadism.